Indium tungsten oxide thin films for flexible high-performance transistors and neuromorphic electronics - Kulkarni, Mohit Rameshchandra (2019)
Thin-film transistors (TFTs) with high electrical performances (mobility > 10 cm2/V s, Vth < 1 V, SS < 1 V/decade, on/off ratio ≈ 106) obtained from the silicon- and oxide-based single-crystalline semiconductor materials require high processing temperature and hence are not suitable for flexible electronics. Amorphous oxide-based transparent electronic devices are attractive to meet emerging technological demands where crystalline oxide-/silicon-based architectures cannot provide a solution. Here, we tackle this problem by using a novel amorphous oxide semiconducting material—namely, indium tungsten oxide (IWO)—as the active channel in flexible TFTs (FTFTs). Post-annealing temperature as low as 270 °C for amorphous IWO thin films deposited by radio frequency sputtering at room temperature could result in smooth morphology (Rrms ≈ 0.42 nm), good adhesion, and high carrier density (n ≈ 7.19 × 1018 cm–3). Excellent TFT characteristics of flexible devices could be achieved with linear field effect mobility μFE ≈ 25.86 cm2/V s, subthreshold swing SS ≈ 0.30 V/decade, threshold voltage Vth ≈ −1.5 V, and on/off ratio Ion/Ioff ≈ 5.6 × 105 at 3 V and stable operation during bending of the FTFT. Additionally, IWO TFTs were implemented as synapses, the building block for neuromorphic computing. Paired-pulse facilitation up to 138% was observed and showed an exponential decay resembling chemical synapses. Utilizing this characteristic, a high-pass dynamic temporal filter was devised providing increased gain from 1.55 to 21 when frequency was raised from 22 to 62 Hz. The high performance and stability of flexible TFTs obtained with IWO films demonstrate their promise for low-voltage electronic applications.